Understanding academic misconduct behaviors among university students during the COVID-19 remote teaching and learning phase - Tengku Azzman, Tengku Siti Aisha; Sedu, Nerawi; Abu Seman, Muhamad Sadry (Universiti Malaya, 2023)
The COVID-19 pandemic has necessitated many higher educational institutions (HEIs) to switch to online learning. In situations rife with academic uncertainties, students and staff had to adjust to this new norm. In this study, we predict that religiosity, social presence, and computer-mediated communication will reduce academic misconduct behaviours. A cross-sectional survey was distributed among HUM undergraduate students (N = 469). Findings indicate that religiosity reduced academic misconduct behaviours and mediated the relationship between social presence and misconduct behaviours. The implication of the study findings on social presence theory, and factors that may influence academic misconduct behaviours, is deliberated.